The Analysis of Rhetorical Styles of World Figures in Public Speaking - Arianto, Tomi; Septriani, Septriani (eScience Humanity Journal, 2023)
This research aims to reveal various rhetorical styles of world figures when delivering their orations/speeches in front of the public from a language style perspective. This research uses a figurative language approach as a theoretical concept. Figurative language is language that "symbolizes" a typical way of expressing thoughts and feelings in mental or verbal form. Abrams (2010) stated that figurative language is part of language style in the form of rhetoric. By using a qualitative descriptive approach, this research reveals several speeches by world figures such as Martin Luther King Jr., John F. Kennedy, Barack Obama, Nelson Mandela, and Soekarno. The results of this research showed that world figures apply a distinctive rhetorical style but can be traced using the styles of Anaphora, Parallelism, Hetorical Questions, Metaphor, Tricolon, Antithesis, Epistrophe, Pathos, Allusion, and Litotes.